Neuro–Techno–Ethno Policy Framework: Menata Ulang Analisis Kebijakan Pendidikan untuk Ekosistem Pembelajaran yang Berkelanjutan dan Responsif Kontekstual - Qoriah Rahmawati Ridho (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study develops an integrative framework for education policy analysis, namely the Neuro–Techno–Ethno Policy Framework (NTEPF), by synthesizing insights from neuroscience, digital transformation, and ethnopedagogy. Contemporary policy approaches tend to operate in fragmented paradigms, limiting their capacity to address complex and context-dependent educational challenges. This research employs a conceptual qualitative design using critical literature synthesis and theory-building methodology. The findings indicate that effective policy depends on the alignment between cognitive processes, technological infrastructures, and cultural contexts. The proposed framework contributes to education policy theory by bridging micro-level learning dynamics with macro-level governance structures. It also provides a practical direction for designing adaptive, inclusive, and sustainable learning ecosystems